The netting efficiencies of marketwide central clearing - Michael J. Fleming; Frank Keane (Federal Reserve Bank of New York, 2021)
Market disruptions in response to the COVID pandemic spurred calls for the consideration of marketwide central clearing of Treasury securities, which might better enable dealers to intermediate large customer trading flows. We assess the netting efficiencies of increased central clearing using nonpublic Treasury TRACE transactions data. We find that central clearing of all outright trades would have lowered dealers' daily gross settlement obligations by roughly 330 billion (60 percent) in the weeks preceding and following the market disruptions of March 2020, but nearly 800 billion (70 percent) when trading was at its highest. We also find that expanded central clearing would have substantially lowered settlement fails. The estimated benefits would likely be greater if dealers' auction purchases were included in the analysis or if the increased central clearing included repo transactions.
Keywords: G28; G18; G12; 330; Treasury securities; central clearing; dealers; market structure; COVID-19